MO930: Does Oral Sodium Bicarbonate Improve Protein Metabolism and Regeneration in Esrd Patients on Maintenance Hemodialysis?. (3rd May 2022) - Ali, Ala; Rashid, Zina
Abstract: BACKGROUND AND AIMS: Uremic metabolic acidosis with decreased bicarbonate levels is frequent in hemodialysis patients, and its correction is one of the goals to achieve adequate dialysis. Unfortunately, the bicarbonate delivered through the dialysate may be inadequate to correct the whole acid load. Most hemodialysis data show that about 50% of patients fail to meet a bicarbonate level within the normal range before each dialysis session. Furthermore, low predialysis bicarbonate levels of <22 mmols/L have been linked with increased malnutrition, inflammation and all-cause mortality in hemodialysis patients.   This study investigates whether oral sodium bicarbonate supplementation in acidotic hemodialysis patients will improve normalized protein catabolic rate (nPCR) and serum albumin as indicators of nutritional adequacy. METHOD: An interventional study was conducted in a trusted hemodialysis unit in Baghdad, Iraq, from 1 September to 1 December 2021. A total of 50 adult prevalent hemodialysis patients were recruited. Out of 50 patients, 26 patients received oral sodium bicarbonate 500 mg/day, and 24 were matched controls. All patients had no significant residual renal function with thrice/week dialysis through arteriovenous fistulae.   Serum albumin and the normalized protein catabolism ratio were measured at baseline and 3 months. In addition, anthropometric measures and essential lab data were recorded, including pre-HD arterial pH, serum bicarbonate, serum creatinine, serum Na, k, body weight, interdialytic weight gain, predialysis systolic and diastolic blood pressure and spKt/V. RESULTS: The mean age of the study group was 48.76 +  16.21 years with 27 females. The median dialysis duration was (3 years). We found no statistically significant difference in the nPCR and serum albumin between the two groups at 3 months.   There was a significant difference in the serum bicarbonate level in the intervention group with a P-value of 0.00. In addition, there were significant differences in arterial PH (P-value 0.008) and serum potassium (P-value 0.039) at 3 months. Serum potassium decreased in the intervention group to the range of (3.9–5.8 meq/L) in comparison to (4.2–6.7 meq/L) in the control group. There was no statistically significant interdialytic weight gain or change in systolic blood pressure at 3 months between the two groups (P-values 0.4 and 0.07), respectively. CONCLUSION: Optimal dialysis dose and acidosis correction are not enough to achieve adequate protein metabolism, indicating poor protein intake by Iraqi HD patients, which mandates proper nutritional counseling.